2015
DOI: 10.1002/ab.21584
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of male sexual aggression from adolescence through college: A latent class growth analysis

Abstract: Approximately 25% of male college students report engaging in some form of sexual coercion by the end of their fourth year of college. White and Smith (2004) found that negative childhood experiences-childhood sexual abuse, childhood physical abuse, and witnessing domestic violence-predicted sexual aggression perpetrated before college, but not during the subsequent college years, a puzzling finding in view of the reasonably consistent rates of sexual aggression from adolescence to the first 2 years of college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 69 publications
4
39
0
Order By: Relevance
“…Current findings add to the extant research suggesting that the etiology of SV is complex and multifactorial (Abbey et al, 2012; Cale, Lussier, & Proulx, 2009; Lussier & Davies, 2011; Swartout et al, 2015) and is explained by exposures at each level of the social ecology. Prior exposure youth have to violent romantic partnerships as modeled by their caregivers ( family -level) predicts subsequent SV perpetration.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Current findings add to the extant research suggesting that the etiology of SV is complex and multifactorial (Abbey et al, 2012; Cale, Lussier, & Proulx, 2009; Lussier & Davies, 2011; Swartout et al, 2015) and is explained by exposures at each level of the social ecology. Prior exposure youth have to violent romantic partnerships as modeled by their caregivers ( family -level) predicts subsequent SV perpetration.…”
Section: Discussionmentioning
confidence: 52%
“…Most longitudinal studies of SV focus on men as perpetrators and women as victims (Abbey & McAuslan, 2004; Maxwell et al, 2003; Swartout et al, 2015; White & Smith, 2009). As a result, much of what is known about SV perpetration is based upon men’s reports.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as the field begins to focus on shared risk and protective factors for violence, it is important to consider the nuances of these subgroups when looking at effectiveness and outcomes of interventions. For example, Swartout et al [35] examined adolescent to emerging adult males and perpetration of sexual violence. They found four trajectories of perpetration: stable low, stable moderate, decreasing, and increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from the U.S. found that about 30% of male college students reported some form of sexually aggressive behavior since adolescence (Swartout et al, 2015; Dardis et al, 2016). In a recent German study, the overall prevalence of male perpetration was lower, but still substantial with 13.2% (Krahé and Berger, 2013).…”
Section: Introductionmentioning
confidence: 99%